2016
DOI: 10.4102/jamba.v8i1.274
|View full text |Cite
|
Sign up to set email alerts
|

Coastal erosion management in Accra: Combining local knowledge and empirical research

Abstract: Coastal erosion along the Accra coast has become a chronic phenomenon that threatens both life and property. The issue has assumed a centre stage of national debate in recent times because of its impact on the coastal communities. Lack of reliable geospatial data hinders effective scientific investigations into the changing trends in the shoreline position. However, knowledge about coastal erosion, by the local people, and how far the shoreline has migrated inland over time is high in the coastal communities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Mentaschi et al (2018) report a coastal area losses of 160 km 2 and 460 km 2 over a 30-year period along the Atlantic and Indian Ocean coasts of the continent. At the more regional level, in Ghana along the Gulf of Guinea about 79% of the shoreline was found to be retreating while 21% was found to be stable or prograding over the period 1974-1996(Addo and Addo, 2016.…”
Section: Coastal Floodmentioning
confidence: 99%
“…Mentaschi et al (2018) report a coastal area losses of 160 km 2 and 460 km 2 over a 30-year period along the Atlantic and Indian Ocean coasts of the continent. At the more regional level, in Ghana along the Gulf of Guinea about 79% of the shoreline was found to be retreating while 21% was found to be stable or prograding over the period 1974-1996(Addo and Addo, 2016.…”
Section: Coastal Floodmentioning
confidence: 99%
“…Recent observations employing digital topographic maps and aerial photogrammetry revealed that 79% of the shoreline is currently experiencing erosion, causing severe damage to coastal structures (Fig. 1e) (Addo & Addo, 2016). Reports of coastal building collapses in Africa are particularly difficult to assess due to the lack of accessible public records, unreported incidents, and local authorities often unable to identify the cause of these structural failures.…”
Section: Global Overview Of Coastal Building Collapsesmentioning
confidence: 99%
“…Many researchers [41,53,57,58] identify the key coastal management policy gaps in Ghana to include: (1) the absence of shoreline management plans (SMPs) to regulate which coastal management policy (HTL, ATL, MR, and NAI) to apply for a particular coast or region; (2) the multiplicity of coastal management regulations; (3) the multiplicity of disjointed coastal management institutions; (4) the non-implementation of coastal management decisions and environmental laws, a culture that has worsened problems of brisk real estate developments, encroachment into wetlands and land degradation [54], and coastal sediment mining [59], altogether contributing to severe coastal erosion and unsustainable coastal changes. Traditionally, exploitation of coastal sediment is considered an endowment that coastal communities have a right to [54,59]; (5) the exclusion of key stakeholders, including coastal communities and research institutions, from coastal management decision-making, from planning to implementation [53].…”
Section: Major Gaps In Coastal Management Policy In Ghanamentioning
confidence: 99%